Vitamin D: prescription audit in tertiary health care centre - Dashputra, Amruta V.; Badwaik, Rupesh T.; Borker, Archana S.; Date, Amit P.; Survase, Priyanka (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Vitamin-D is critically important for development, growth and maintenance of health of human being. Many evidences show association between vit-D deficiency and several serious health conditions. Data collection on use of drugs is being obtained with the aim of optimizing drug therapy. So far till date only few studies about prescription pattern of vit-D have been found. Hence it is very important to do audit of prescriptions of vit-D. The aim of the study is to provide concise and updated information about the use of vit-D in tertiary care hospital and to record demographic details of patients. Methods: After ethical approval, this cross sectional study was conducted at tertiary health centre. Patient and drug data (name of drug, dose, dosage form and route of administration) was collected from the patient’s prescriptions in OPD. Results: Highest prescriptions of vit-D were found in orthopedic department (22% of total prescriptions of that department). Prescribing percentage of vit-D in medicine department was 4.6%, dermatology 1.5% and in psychiatry 0.8% of total prescriptions. Prescriptions of vit-D in combination with calcium were found in orthopedics (52%), medicine (7%) and obstetrics and gynecology (10%) departments. Conclusions: Highest prescriptions of vit-D alone and with calcium found in orthopedic department. Periodic therapeutic audit is necessary to rationalise the use of vit D.